Mast Cell-Targeted Strategies in Cancer Therapy - Ammendola, Michele (Transfus Med Hemother, 2016)
Mast cells (MCs) are cells that originate in the bone marrow from pluripotent CD34+ hematopoietic stem cells. Precursors of MCs migrate through the circulation to their target tissues, completing their maturation process into granulated cells under the influence of several microenvironment growth factors. The most important of these factors is the ligand for the c-Kit receptor (c-Kit-R) namely stem cell factor (SCF), secreted mainly by fibroblasts and endothelial cells (ECs). SCF also regulates development, survival and de novo proliferation of MCs. It has already been demonstrated that gain-of-function mutations of gene c-Kit encoding c-Kit-R result in the development of some tumors. Furthermore, MCs are able also to modulate both innate and adaptive immune response and to express the high-affinity IgE receptor following IgE activation. Among the other IgE-independent MC activation mechanisms, a wide variety of other surface receptors for cytokines, chemokines, immunoglobulins, and complement are also described. Interestingly, MCs can stimulate angiogenesis by releasing of several pro-angiogenic cytokines stored in their cytoplasm. Studies published in the last year suggest that angiogenesis stimulated by MCs may play an important role in tumor growth and progression. Here, we aim to focus several biological features of MCs and to summarize new anti-cancer MC-targeted strategies with potential translation in human clinical trials.